Comparison of Agatston Score Calculation Between the Syngo.Via Automated Method and the Manual Method in Non-Contrast Cardiac CT - Muaziz, Agil Abdul; Utami, Hernastiti Sedya; Oviyanti, Pradana Nur; Supriyadi, Supriyadi; Nugraha, Fathur Rahman (Syntax Corporation Indonesia, 2026)
In clinical practice, the Agatston Score can be calculated manually or automatically using post-processing software such as Syngo.Via; However, the difference in absolute values between these methods can affect clinical interpretation. The study aimed to compare measurements of the Agatston Score obtained using the Syngo.Via automated method and manual calculations on non-contrast cardiac CT, with an emphasis on measurement differences, suitability, and reliability. A quantitative observational analytical study was conducted using retrospective no-contrast cardiac CT data from 20 subjects. The Agatston score is calculated automatically using Syngo.Via and manually using the Weasis software on the same image dataset. The difference in measurement was analyzed descriptively and tested for normality. Statistical differences were evaluated using the Wilcoxon Signed Rank Test, suitability was evaluated using Bland–Altman analysis, and reliability was evaluated using the Intraclass Correlation Coefficient (ICC) with a two-way mixed effect model and absolute suitability. Results showed that a difference between the method was not normally distributed and a statistically significant difference in the Agatston score was observed (p < 0.05). The Bland–Altman analysis showed that most of the differences were distributed around the zero line with a few outliers, while the ICC analysis revealed a very high reliability between the two methods (ICC = 1,000). In conclusion, the automatic and manual measurement of the Agatston Score showed excellent reliability and good agreement despite the statistically significant differences in absolute values, suggesting that the two methods could be compared.